THE LEGITIMACY OF INCREASING MARGINAL UTILITY IN SOCIAL SERVICES – THE CASE OF UNIVERSITY EXAMINATIONS - Filipic, Petar (Economic Annals, 2010)
The concept of utility became rightfully recognised in economic theory with the introduction of decreasing marginal utility. However a question that arises is: does an increasing consumption of goods always and without exception lead to diminishing marginal utility? It is quite possible that in some cases marginal utility of goods and services actually increases. If this fact is true, it might additionally strengthen the utility theory and make it applicable in numerous cases of economic and social reality. This paper uses the example of the utility of studying at university (i.e. the utility of university examinations), and tries to add a few arguments in favour of the statement that the law of increasing utility exists.